Loss of chloroplast DNA methylation during dedifferentiation of Chlamydomonas reinhardi gametes. - Sano, H (1984)
In Chlamydomonas reinhardi the chloroplast DNA (ch;DNA) of mating type plus cells undergoes cyclical methylation and demethylation during the life cycle. Methylation occurs during gametogenesis, and fully differentiated gametes can be dedifferentiated back to vegetative cells which contain nonmethylated chlDNA by the addition of a nitrogen source for growth. We examined the dedifferentiation process and found that the mating ability of gametes was lost rapidly after the start of dedifferentiation at a time when the chlDNA was still methylated. The enzymatic activity of the 200-kilodalton DNA methyltransferase was lost at a rate consistent with the rate of dilution during cell division. Methylation of chlDNA decreased at a slower rate than was expected from cell division alone but was consistent with the continuing activity of the preexisting methyltransferase so long as it was present. These results support the hypothesis that demethylation of chlDNA occurs by dilution out of enzymatic methylating activity rather than by enzymatic demethylation.